Ficus squamosa Roxb. (Moraceae) A NEW RECORD FOR THE FLORA OF VIETNAM - Nguyen Trung, Thanh; Oanh, Pham Thi; Xuyen, Do Thi; Duc, Nguyen Anh; Hai, Do Van (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3DO - 10.25073/2588-1140/vnunst.4649, 2017)
Abstract: During the study of the literature, collecting specimens from the field and studying the specimens of Ficus genus in herbarium and international botanical specimens, we found the species: Ficus squamosa , a new record for flora of Vietnam. It is closed to Ficus hispida and chiefly differs in caespitose habit and lateral bracts present on fig body. In this paper, we introduce for this species with a short data on taxonomy, types, morphology, ecology and distribution of the mentioned species accompanied with the photos. The vouchers were collected in Cham Chu special used forest (Tuyen Quang province), preserved in the Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN) and VNU-University (HNU).